Population attributable risks of oral cavity cancer to behavioral and medical risk factors in France: results of a large population-based case–control study, the ICARE study - Radoï, Loredana (BMC Cancer, 2015)
BACKGROUND: Population attributable risks (PARs) are useful tool to estimate the burden of risk factors in cancer incidence. Few studies estimated the PARs of oral cavity cancer to tobacco smoking alone, alcohol drinking alone and their joint consumption but none performed analysis stratified by subsite, gender or age. Among the suspected risk factors of oral cavity cancer, only PAR to a family history of head and neck cancer was reported in two studies. The purpose of this study was to estimate in France the PARs of oral cavity cancer to several recognized and suspected risk factors, overall and by subsite, gender and age. METHODS: We analysed data from 689 oral cavity cancer cases and 3481 controls included in a population-based case–control study, the ICARE study. Unconditional logistic regression models were used to estimate odds ratios (ORs), PARs and 95 % confidence intervals (95 % CI). RESULTS: The PARs were 0.3 % (95 % CI −3.9 %; +3.9 %) for alcohol alone, 12.7 % (6.9 %–18.0 %) for tobacco alone and 69.9 % (64.4 %–74.7 %) for their joint consumption. PAR to combined alcohol and tobacco consumption was 74 % (66.5 %–79.9 %) in men and 45.4 % (32.7 %–55.6 %) in women. Among suspected risk factors, body mass index 2 years before the interview <25 kg.m(−2), never tea drinking and family history of head and neck cancer explained 35.3 % (25.7 %–43.6 %), 30.3 % (14.4 %–43.3 %) and 5.8 % (0.6 %–10.8 %) of cancer burden, respectively. About 93 % (88.3 %–95.6 %) of oral cavity cancers were explained by all risk factors, 94.3 % (88.4 %–97.2 %) in men and only 74.1 % (47.0 %–87.3 %) in women. CONCLUSION: Our study emphasizes the role of combined tobacco and alcohol consumption in the oral cavity cancer burden in France and gives an indication of the proportion of cases attributable to other risk factors. Most of oral cavity cancers are attributable to concurrent smoking and drinking and would be potentially preventable through smoking or drinking cessation. If the majority of cases are explained by recognized or suspected risk factors in men, a substantial number of cancers in women are probably due to still unexplored factors that remain to be clarified by future studies.